The University Identity: Communication of Identity Themes - BÃ¼k, Tuba Bozaykut; Duman, Åžirin Atakan-; PaÅŸamehmetoÄŸlu, AyÅŸÄ±n (International Business and Accounting Research Journal, 2017)
Â Earlier research has brought organizational identity to the fore as an institutional response to the developments in higher education field. Following literature, this study aims to examine the organizational identity of universities through an analysis of themes communicated at their websites. The study findings reveal that participant universities communicate five common identity themes institutionalized by higher education field. Among these themes, social values presented to the society for belongingness and capacity for enriching main university functions are found out to be most communicated themes. The findings also show that each university communicates distinct themes that still fall under these five common themes. Therefore, the study presents that distinct themes symbolizing the uniqueness claim of the university identity emerge within the pre-determined theme categories in the field.